Picturing Research
XIV, 244 p.
Keywords: Picturing research: drawing as visual methodology offers a timely analysis of the use of drawings in qualitative research. Drawing can be a method in itself, as in the research area of Visual Studies, and also one that complements the use of photography, video, and other visual methodologies. This edited volume is divided into two sections. The first section provides critical commentary on the use of drawings in social science research, addressing such issues of methodology as the politics of working with children and drawing, ethical issues in working with both adults and children, and some of the interpretive considerations. The second section, in its presentation of nine research-based case-studies, illustrates the richness of drawings. Each case study explores participatory research involving drawings that encourages social change, or illustrates participant resilience. These case studies also highlight the various genres of drawings including cartoons and storyboarding. The book draws on community-based research from a wide variety of contexts, most in South Africa, although it also includes work from Rwanda and Lesotho. Given the high rates of HIV&AIDS in sub-Saharan Africa, it should not be surprising that many of the chapters take up concerns such as the preparation of teachers and community health workers in the age of AIDS, and the experiences of orphans and vulnerable children. Moving further afield, this book also includes work done with immigrant populations in Canada, and with tribunals in Somalia and Australia. Picturing research is an important resource for novice and experienced researchers interested in employing qualitative methodology that encourages rich (yet low-tech) visible data and that offers a participatory, enabling experience for participants and their communities.